Beyond 'Technology for Development' and 'Sustainability' towards Syste mic and Holistic Rural Innovation: Success Factors from the Southern A frican Experience over 20 years - Buisson, Uys Du; Cronje, Braam; Marais, Mario; Haruperi, Emmanuel; Rensburg, Johann
Abstract: This paper describes essential, real-world activities and pr ocesses needed to develop and deploy people-centred networks enabled w ith innovative technologies that in turn produce "...